Effect of aluminum on the absorption and translocation of phosphorus and on the mineral composition of two cultivars of wheat - Alves, Vera Maria Carvalho; Novais, Roberto Ferreira de; Neves, Júlio César Lima; Barros, Nairam Félix de (Pesquisa Agropecuaria Brasileira, 2014)
The effect of aluminum on the kinetic of absorption and translocation of phosphorus and mineral composition of Anahuac (sensitive) and BH-1146 (tolerant) wheat cultivars was measured. Aluminum at the levels of zero and 0.5 mg.l-1was used during the growth period except when the experiment on the kinetics of P-absorption and translocation was carried out. Aluminum reduced the Vmax of both cultivars although this effect was greater for the BH-1146 cultivar. It caused also some reduction on the Km of this cultivar and an increase for the Anahuac. Aluminum caused a reduction on the phosphorus translocation in the Anahuac and an increase in the BH-1146. Aluminum also caused differences between the cultivars in Ca, Zn and Mn concentration in the shoots and in P, Mg and Fe in the root system. In general, the BH-1146 presented higher concentrations of cations than the Anahuac with or without aluminum in solution. The differential tolerance of the cultivars to aluminum seems to be related to the absorption and translocation, not only of phosphorus but also of other nutrients.